Development Of A System Dynamics Model For Blue Economy-Based Tourism Destinations As An Effort To Identify New Sustainable Growth Sources In The Pacet Region, Mojokerto - Agustina, Ratna; Dewianawati, Dwi; Setyaasih, Setyaasih (JURNAL MANAJEMEN MOTIVASI, 2026)
This study develops a System Dynamics model for a Blue Economy-based tourism destination in Pacet, Mojokerto. Using Python-based simulations, it identifies key variables, constructs causal loop and stock-flow diagrams, and evaluates policy scenarios. Results reveal a decline in tourist numbers from 10,000 to 8,421 and environmental degradation to zero, even with conservation investments. The findings indicate that partial conservation policies are ineffective, highlighting the need for a systemic and integrative approach to sustain tourism growth and ecological balance.